Descriptive study of gastrointestinal manifestations in HIV/AIDS - Koshy, Varghese; Koshy, George; Gangadharan, Vandana (International Journal of Research in Medical Sciences, 2018)
Background: Acquired Immunodeficiency Syndrome (AIDS) was first recognized in 1981 as a clinical syndrome consisting of opportunistic infections and /or neoplasia associated with uneplained immunodeficiency. The gastrointestinal tract is one of the most common sites of clinical affection of AIDS and all levels from the oral cavity to the anus are frequently involved. Methods: A cohort of 70 HIV positive patients, admitted in a tertiary level referral hospital, were studied for symptoms of gastrointestinal disease and patients with clinical or investigative findings of gastrointestinal disease were clinically examined and then subjected to further relevant investigations. Results: The prevalence of GI menifestations in this cohort was 71.4%. The mean age of the study population was 36 years. Amongst frequency of GI manifestations, diarrhoea was found in 26 patients (52%), of whom 77% (20 out of 26) had diarrhoea lasting longer than one month and amongst the patients with oral ulcers, oral candidiasis was the most common oral manifestation, present in 87% of them. Cryptosporidium was the most common organism isolated from the stool samples. Conclusions: The most common presenting complaints were oral ulcers and chronic diarrhoea amongst the cohort examined in this study.